2015
DOI: 10.1007/s12526-015-0346-4
|View full text |Cite
|
Sign up to set email alerts
|

Notes on metazoan parasites of Alepisaurus ferox and Xiphias gladius of the eastern Arabian Sea

Abstract: Documentation of fish parasites is important in describing the biodiversity of a given water body. In this study, the first record of metazoan parasite fauna of long snouted lancetfish (Alepisaurus ferox) and swordfish (Xiphias gladius) of the eastern Arabian Sea is presented. Three cestodes (Pelichnibothrium speciosum, Tentacularia coryphaenae and Hepatoxylon trichiuri) and one trematode (Botulus microporus) were collected from the lancetfish. Parasite prevalence was 98.04 % and the average intensity was 9.58… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Given ongoing climate change, this is a particularly important issue, especially as swordfish are migratory fish, travelling long distances to feed, which can be particularly conducive to parasite expansion. To date, more than 70 parasite species have been documented in X. gladius, most of which are helminths, including species with a wider host range and high zoonotic importance (Palko et al 1981;Hogans et al 1983;Dubina 1985;Williams & Bunkley-Williams 1996;Caton et al 1998;Speare 1999;Castro-Pampillón et al 2002a,b;Garcia et al 2008Garcia et al , 2011Mattiucci et al 2014;Varghese & Unnikrishnan 2016;De Silva et al 2017). The present paper describes a preliminary study concerning a unique record of Philichthys xiphiae Steenstrup, 1862, a rarely observed and poorly studied parasitic copepod from the family Philichthyidae.…”
Section: Introductionmentioning
confidence: 99%
“…Given ongoing climate change, this is a particularly important issue, especially as swordfish are migratory fish, travelling long distances to feed, which can be particularly conducive to parasite expansion. To date, more than 70 parasite species have been documented in X. gladius, most of which are helminths, including species with a wider host range and high zoonotic importance (Palko et al 1981;Hogans et al 1983;Dubina 1985;Williams & Bunkley-Williams 1996;Caton et al 1998;Speare 1999;Castro-Pampillón et al 2002a,b;Garcia et al 2008Garcia et al , 2011Mattiucci et al 2014;Varghese & Unnikrishnan 2016;De Silva et al 2017). The present paper describes a preliminary study concerning a unique record of Philichthys xiphiae Steenstrup, 1862, a rarely observed and poorly studied parasitic copepod from the family Philichthyidae.…”
Section: Introductionmentioning
confidence: 99%